2022
DOI: 10.4103/gmit.gmit_30_22
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hysterectomy Trends in the Last 5 Years at a Tertiary Center

Abstract: Objectives: This study aimed to assess trends by evaluating the types and complications of hysterectomies performed for benign gynecological reasons at our clinic, which is one of the largest hospitals in Turkey. Materials and Methods: Hysterectomies performed for benign reasons at our gynecology and obstetrics clinic between January 1, 2015 and December 31, 2020 were retrospectively reviewed and included in the analysis. Of the 4288 patients who had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There are different surgical procedures defined in hysterectomies performed for benign gynecological pathologies. Approximately 20% to 40% of women in every developed and developing country have undergone hysterectomy at the age of 60 (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different surgical procedures defined in hysterectomies performed for benign gynecological pathologies. Approximately 20% to 40% of women in every developed and developing country have undergone hysterectomy at the age of 60 (1).…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the demographic characteristics of the participants in this study. It was observed that the average age of group I was 59.15 years, and the average age of group II was 54.73 years, which was significantly different (p = 0.058).…”
mentioning
confidence: 99%